Developing Virtual Reality-Based Learning Media in Introduction to Psycholinguistics Class - Rifki Oktoviandry; M. Affandi Arianto; Rita Arni (Universitas Negeri Padang, 2023)
Learning media is one of the most important components in the teaching and learning process. Without learning media, the teaching and learning process tends to be stiff and boring. The need for creative, interactive and innovative learning media is very important because the characteristics of today's students are very much different compared to previous generations. Generation Z, which is currently studying in tertiary institutions, is a generation that was born and grew up with digital technology. Conventional methods and media are no longer suitable for this generation. Therefore, teachers need to implement digital technology-based learning. This research aims to develop learning media based on Virtual Reality in the Introduction to Psycholinguistics course. The research method used is the Research and Development (RnD) research method with the ADDIE approach (Analysis, Designing, Development, Implementation and Evaluation). The results show that Virtual Reality-based learning media is valid and practical to be used in Introduction to Psycholinguistics Class. Despite of the validity and practicality, some minor revisions still ne needed.